STUDI PEMBUATAN SELAI BUNGA ROSELLA (Hibisscus sabdariffa L.) - Budi Suarti Suarti; Desi Ardilla; Ahmad Jubeir (AGRIUM: Jurnal Ilmu Pertanian, 2011)
AbstractThis study to determine the effect of the amount of sugar and pectin to the quality of rosella flower butter. This study uses a Complete Randomized Design (CRD) with factorial (2) of two replicates. Factor I is the amount of sugar with a password (G) consisting of 4 standard, namely: G0 = 45%, G1 = 50%, G2 = 55% and G3 = 60%. Factor II is the amount of pectin with a password (P) which consists of four standards are: P1 = 0.2%, P2 = 0.4%, P3 = P4 = 0.6% and 0.8%. The parameters observed include: TSS, levels of Vitamin C, total acid, organoleptic taste and texture.Keywords: sugar, pectin, butter, rosella